Sexual differences in the foraging behaviour of Magellanic Penguins related to stage of breeding - Raya Rey, Andrea Nélida (2012)
Understanding the foraging behaviour of seabirds and its plasticity is vital to establish their role in marine food webs and their use as indicators of change in the availability of prey. The foraging behaviour of penguins is known to differ with locality, sex, stage of breeding and between years. We studied the diving behaviour of breeding Magellanic Penguins (Spheniscus magellanicus), using time-depth recorders, during incubation and brooding in the 200304 and 200405 breeding seasons at Isla Martillo, Tierra del Fuego, Argentina. Foraging trips during the incubation period were longer than those during the brooding period for both sexes in both years of the study. Sex-related differences in foraging behaviour were observed during the incubation stage. During the incubation stage females performed longer foraging trips than males, foraging effort was lower, and did not dive as deep as males in both years. Foraging success was lower for females than males during incubation only in 2003. Our results suggest that sexual differences, expressed as differences in the foraging parameters of males and females, only develop when Fuegian Sprat (Sprattus fuegensis), the main prey in this locality, is not abundant close to the colony. Females may be extending the volume of water they can exploit by extending the duration of trips (horizontal distance), whereas males do so by diving deeper (vertical distance). Our results show the fundamental differences in foraging strategies between the sexes in Magellanic Penguin are a consequence of environmental conditions not morphological differences between sexes.